2021
DOI: 10.1111/jace.17856
|View full text |Cite
|
Sign up to set email alerts
|

Efficient near‐infrared pyroxene phosphor LiInGe2O6:Cr3+for NIR spectroscopy application

Abstract: Broadband near‐infrared phosphors are essential to realize nondestructive analysis in food industry and biomedical areas. Efficient long‐wavelength (>830 nm) phosphors are strongly desired for practical applications. Herein, we demonstrate an efficient broadband NIR phosphor LiInGe2O6:Cr3+, which exhibits a broad NIR emission peaking at ~880 nm with a full width at half maximum of 172 nm upon 460 nm excitation. The internal/external quantum efficiencies of LiInGe2O6:Cr3+ are measured to be 81.2% and 39.8%, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(53 citation statements)
references
References 38 publications
(41 reference statements)
0
50
0
1
Order By: Relevance
“…For instance, Liu et al reported LiInGe 2 O 6 :Cr 3+ with 81.2% internal quantum efficiency (IQE) and a full width at half maximum (FWHM) of 172 nm. 17 Basore et al reported a highly thermally stable garnet Ga 3 Sc 2 Ga 3 O 12 :Cr 3+ phosphor, and the IQE of the phosphor significantly improved to 98.6% after co-doping with Al 3+ ions. 18 Rajendran et al reported La 3 Ga 5 GeO 14 :Cr 3+ , which had two different crystallographic Cr 3+ sites and thus showed super broad NIR emissions with an FWHM of B330 nm.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Liu et al reported LiInGe 2 O 6 :Cr 3+ with 81.2% internal quantum efficiency (IQE) and a full width at half maximum (FWHM) of 172 nm. 17 Basore et al reported a highly thermally stable garnet Ga 3 Sc 2 Ga 3 O 12 :Cr 3+ phosphor, and the IQE of the phosphor significantly improved to 98.6% after co-doping with Al 3+ ions. 18 Rajendran et al reported La 3 Ga 5 GeO 14 :Cr 3+ , which had two different crystallographic Cr 3+ sites and thus showed super broad NIR emissions with an FWHM of B330 nm.…”
Section: Introductionmentioning
confidence: 99%
“…The visible region of the solar spectrum can be achieved by commercial phosphors excited by blue LED chips. To meet the requirements of broad-spectrum emission and high efficiency of pc-LEDs, the NIR region usually requires using high-performance NIR luminescent materials doped with Cr 3+ ions [12][13][14][15][16][17][18][19][20][21]. Zeng et al [22] reported Cr 3+ -doped double perovskite La 2 MgZrO 6 , demonstrating broadband NIR emission centered at 825 nm with~58% luminescence internal quantum efficiency (IQE).…”
Section: Introductionmentioning
confidence: 99%
“…The 350 nm peak probably originates from the combination of host absorption and 4 A 2 ( 4 F) -4 T 1 ( 4 P) transition of Cr 3+ . 18 The other two absorption bands, 400-550 nm and 600-800 nm, can be attributed to the 4 A 2 ( 4 F) -4 T 1 ( 4 F) and 4 A 2 ( 4 F) -4 T 2 ( 4 F) transitions of Cr 3+ , respectively. 18 Besides, a weak absorption band near 700 nm appears in all the samples, which can be attributed to the spin-forbidden 4…”
Section: Luminescence Propertiesmentioning
confidence: 94%